Topological and lattice-based AM optimization for improving the structural efficiency of robotic arms - Batista, Rafael Cavicchioli; Agarwal, Abhishek; Gurung, Adash; Kumar, Ajay; Altarazi, Faisal; Dogra, Namrata; H. M., Vishwanatha; Chiniwar, Dundesh S.; Agrawal, Ashish (Frontiers in Mechanical Engineering, 2024)
The robotic arm is one of the vital components of robot assembly. The purpose of the robotic arm is to transmit power and conduct the desired motion i.e., translation or rotation. Robotic limbs are designed and constructed to execute certain tasks with a high degree of speed, accuracy, and efficiency. This research focuses on to enhancing the strength-to-weight ratio of robotic arm using certain techniques of additive manufacturing i.e., topology optimization and lattice structure. Employing the finite element analysis, the impact of weight reduction optimization on structural parameters such as stress and deformation in the current design is assessed using ANSYS R18.1 for FE analysis and Creo parametric 7.0 design software for CAD modeling. Observations reveal that the 0.5 and .4 scale lattice structure designs have deformation of 0.01453mm and 0.01453mm respectively though the generic design has 0.01043mm deformation. Notably, the 0.5 scale lattice of the robotic arm exhibits a 31.08% higher equivalent stress than the generic design with 29.3%. reduction in mass of the robotic arm. These findings highlight the efficacy of lattice structures for optimizing the robotic arm's performance, contributing to advancements in power-efficient robot assembly processes.